Equations of motions and velocities of longitudinal waves for superfluid ³He–A filled aerogel in the presence - Kekutia, Sh.E.; Chkhaidze, N.D. (Физика низких температур, 2008)
We have determined the dynamic equations for superfluid ³He–A filled aerogel in finite magnetic fields. The speeds of propagating longitudinal modes for this system have been found for A₁ and A phases. We have shown that sound phenomena in case ³He–A₁ superfluid are modified from those for He II superfluid.